Research Progress of Electrostatic Water Treatment Technology. Issue 1 (August 2021) - Liu, Zhan; Yan, Meifang; Gao, Yuhua; Li, Haihua; Li, Na; Liu, Zhenfa
Abstract: In recent years, due to the increasing of environmental pressure, the complicated process of chemical treatment and the pollution caused by sewage to the water, it has become the general trend of the current development to search for the treatment technology of industrial circulating cooling water with low energy consumption, water saving and emission reduction. Physical method is simple to operate, non-toxic and pollution-free, no secondary pollution. As one of the commonly used physical water treatment technologies, the study of electrostatic water treatment technology has important significance. This paper studies and summarizes its research, hoping to further clarify the effect and mechanism of electrostatic water treatment technology on the basis of previous studies.